2015
DOI: 10.3329/bjz.v41i2.23316
|View full text |Cite
|
Sign up to set email alerts
|

Population status of oribi (Ourebia ourebi Zimmermann, 1783) in Maze National Park, southern Ethiopia

Abstract: Abstract:The population status of oribi (Ourebia ourebi Zimmermann, 1783) was carried out in the newly established Maze National Park, Ethiopia for two consecutive years (October 2009 to December 2011). A total count method was employed based on silent detection method in an area of 220 km 2 . A total of 894 and 1103 individuals were counted during the two consecutive years, respectively. Seasonal variation was significantly different with more individuals during the dry season than the wet season (p<0.05). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Due to the differences in economic development, social culture, and resource endowment of each country or region, the public's concern and awareness about the establishment and development of national parks are also different [15] (Keigley et al, 2018). For instance, 55.65% of the community residents in southern Ethiopia have a negative attitude towards wildlife conservation, while 18.26% of them are indifferent to reserve management, and public participation in national parks is low, resulting in lions and other wildlife not being effectively protected and even being killed in retaliation [16] (Tekalign et al, 2016). Meanwhile, in Slovakia, 45% of respondents have a positive attitude towards the establishment of national parks, 29.5% have a neutral attitude, and 25.5% have a negative attitude, and personal economic status, relationship with tourism, age, education, and occupation affect the attitude of local people towards national parks [17] (Janetta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the differences in economic development, social culture, and resource endowment of each country or region, the public's concern and awareness about the establishment and development of national parks are also different [15] (Keigley et al, 2018). For instance, 55.65% of the community residents in southern Ethiopia have a negative attitude towards wildlife conservation, while 18.26% of them are indifferent to reserve management, and public participation in national parks is low, resulting in lions and other wildlife not being effectively protected and even being killed in retaliation [16] (Tekalign et al, 2016). Meanwhile, in Slovakia, 45% of respondents have a positive attitude towards the establishment of national parks, 29.5% have a neutral attitude, and 25.5% have a negative attitude, and personal economic status, relationship with tourism, age, education, and occupation affect the attitude of local people towards national parks [17] (Janetta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This finding supportsTortato et al (2015);Woodroffe et al (2007);Patterson et al (2004) who reported that good livestock husbandry (occasions where there is attentive attendance of livestock to prevent them from carnivore attack) reduces opportunities for predation and is a necessary tool to minimise conflict.Local people reported low prey density as a possible indirect factor driving a conflict in the study area. MzNP report and field observation also revealed a low density of wild herbivores, particularly Buffalo (Bubalus bubalis) and Orbi (Ourebia ourebi) Tekalign and Bekele (2016). reported that herbivore species including African buffalo and Orbi were hunted often in the study area.…”
mentioning
confidence: 71%
“…MzNP report and field observation also revealed a low density of wild herbivores, particularly Buffalo ( Bubalus bubalis ) and Orbi ( Ourebia ourebi ). Tekalign and Bekele (2016) reported that herbivore species including African buffalo and Orbi were hunted often in the study area. This puts low natural prey density as the third driving force of depredation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The population size of Bohor reedbuck was determined using the total count method (Norton-Griffiths, 1978;Sutherland, 1996) by dividing the study area into seven different blocks based on the topographic features (Afework et al, 2009;Yihune and Bekele, 2012;Habtamu et al, 2012;Tekalign and Bekele, 2011). Topographic conditions, such as the presence of fixed natural and artificial landmarks, were used to divide the counting blocks to mitigate double counting.…”
Section: Population Sizementioning
confidence: 99%
“…Continuous focal animal observations were used to collect the data on the activity patterns of Bohor reedbuck by recording the activities of a group of Bohor reedbuck in different habitat types with five minutes intervals of one sample record (Afework et al, 2009). Observations were carried out by identifying appropriate locations to record with appropriate distance (between 50 and 300 m) from different directions of each habitat type (Taylor et al, 2006;Afework et al, 2009;Tekalign and Bekele, 2015). The study area was stratified into four habitat types, namely, Acacia dominated wooded grassland, Riverside forest, Open grasses land and Farmland.…”
Section: Activity Patternsmentioning
confidence: 99%